COMPARATIVE ANALYSIS OF THE CULTURAL ASPECTS OF VERBAL REPRESENTATION OF ENVIRONMENTAL EVENTS IN ENGLISH AND RUSSIAN - Mirzayev Jasur; Madalov Navruz (Innovate Conferences, 2025)
The relevance of the research is due to the growing attention to environmental issues and their reflection in the linguistic picture of the world. The aim of the work is to identify linguistic and cultural features of the representation of environmental events in English and Russian.
Keywords: environmental discourse, linguistics, comparative analysis, English, Russian, media texts.